A new species and new distribution records of Zercon C. L. Koch from Iran (Acari: Zerconidae). Issue 4 (2nd October 2018) - Kavianpour, Mohammadreza; Karaca, Mehmet; Karimpour, Younes; Urhan, Raşit
Abstract : A new species of the family Zerconidae, Zercon persicus sp. n., is described based on female and male morphological characters. It was collected in West Azarbaijan province (northwestern Iran). Idiosomal chaetotaxy, poroidotaxy and related notations are illustrated. The similarities and differences between the related species within the genus are discussed. Records of some other Zercon species from the province are given for the first time. http://www.zoobank.org/urn:lsid:zoobank.org:pub:3D1122C7-2B86-40D2-974E-EE69035A2413